2019
DOI: 10.1086/701675
|View full text |Cite
|
Sign up to set email alerts
|

Association between unconventional oil and gas (UOG) development and water quality in small streams overlying the Marcellus Shale

Abstract: Unconventional oil and gas (UOG) development has increased dramatically in the Marcellus Shale region over the past decade, and there is widespread public concern about the potential effects that UOG development may have on water quality. The goal of this study was to assess whether a suite of stream water quality constituents was related to the intensity of UOG development in corresponding catchments. Nineteen streams in southwestern Pennsylvania, where UOG development is prevalent, and 10 streams in western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Previous studies have shown significant effects downstream from discharges from municipal and industrial wastewater treatment plants treating produced water (26,30) and shale gas wastewater disposal facilities (29), and large spill events (24,28,29), but the regional effects of shale gas development on stream environments remain unclear. Previous work has also shown an inability to confidently identify an OG signal when faced with other land uses (8), which are more likely to cooccur in a watershed as size increases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown significant effects downstream from discharges from municipal and industrial wastewater treatment plants treating produced water (26,30) and shale gas wastewater disposal facilities (29), and large spill events (24,28,29), but the regional effects of shale gas development on stream environments remain unclear. Previous work has also shown an inability to confidently identify an OG signal when faced with other land uses (8), which are more likely to cooccur in a watershed as size increases.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for the As in groundwater was not identified, and it was noted that the mobilization of geogenic constituents into private wells could have been caused by mechanical disturbances from intense drilling activity, reduction of the water table by drought or groundwater withdrawals, and faulty gas-well drilling equipment or well casings (Fontenot et al, 2013). Knee and Masker (2019) evaluated whether stream water quality constituents, including As, were related to the intensity of UOG development in catchments in the Marcellus Shale region. They found significant positive relationships between As concentration in streams and UOG well density but the mechanism of mobilization was not identified.…”
Section: Arsenic In Drinking Water/stream Water From Oil and Gas Productionmentioning
confidence: 99%
“…These wastes contain high levels of salts such as barium, benzene, etc., 244 which are rich in radionuclides, where the liquid part of the waste is ltered to the ground water, causing serious radioactive contamination. 232,[245][246][247][248] Impact on surface water. 8,138,225,249 All effluents from the oil and gas industry such as produced water, washing water for rigs, drilling machines, maintenance and repair, oil grease contaminated water, liquid sludge, etc., may contain radioactive materials.…”
Section: The Main Forms Of Petroleum Pollution Tenormsmentioning
confidence: 99%